Identification of pathogenic bacteria by biosensors in water and wastewater - Sakineh Hargolzadeh; Soheila Kashanian; Maryam Nazari (Journal of Applied Research in Water and Wastewater)
Pathogenic microorganisms, such as Escherichia coli, Salmonella, Pseudomonas aeruginosa, Mycobacterium tuberculosis, Staphylococcus aureus, Klebsiella pneumoniae, legionella, Shigella and etc. can contaminate drinking water and lead to disease and even death. On the other hand, due to the ability of antibiotics to prevent or treat bacterial infections, they have been used as the main method of infection treatment in humans and animals for the past two decades. The irresponsible use of these antibiotics is one of the most important reasons for the emergence of microbial resistance, which has become a global issue. Therefore, timely diagnosis of these pathogens is very important. the use of specialized personnel, machines, and tools in molecular methods such as enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) are expensive, and traditional methods such as plate culture are time-consuming. Today, a variety of biosensors are reported to identify these bacteria, which are fast, accurate, and cost-effective. In this review, we described a number of important pathogenic bacteria and biosensors made to identify these pathogens.